Can molecular model crop rice become a boon towards progress of groundnut functional genomics? Can molecular model crop rice become a boon towards progress of groundnut functional genomics? - B SUKRUTHA; SRIVIDHYA AKKAREDDY (Journal of Oilseeds Research, 2023)
Improvement through conventional breeding is a big problem in developing diverse lines of groundnut on tackling good seed quality. A total of 25 markers targeting 13 known rice genes were evaluated with 24 groundnut genotypes and two wild groundnut genotypes (Arachis glabrata, Arachis villosa) and a local popular rice variety NLR34449 (Nellore Mashuri) as molecular check. It was very interesting to note that amplification of 17 (11genes) out of 25 rice gene tagged markers (GTMs) in groundnut accounted for 68% transferability. The analysis of transferability of rice GTMs at individual peanut genotype level revealed a range of 79.17% to 91.67%. This confirmed the possibility of use of the rice markers/genes in groundnut.